Manufacturing maritime firms’ environmental behaviors: theory and practice - Mao, Shuling; Xu, Yinxiao (Frontiers in Marine Science, 2024)
Analyzing the factors that influence maritime manufacturing firms’ environmental behavior is of significant theoretical and practical importance, particularly from a managerial cognition perspective. This study applies the regulatory focus theory to examine the complex relationship between environmental quality, regulation, and firms’ environmental actions. Our findings reveal a U-shaped relationship between regional environmental quality and local firms’ environmental consciousness. In regions with either better or poorer environmental conditions, firms demonstrate higher environmental consciousness. Specifically, firms in regions with better environmental quality exhibit a “promotion focus” on environmental issues, leading to proactive engagement in green innovation. Conversely, firms in regions with poor environmental quality adopt a “prevention focus” by pursuing ISO 14001 certification to maintain legitimacy and mitigate penalties. Moreover, we find that incentive regulations are more effective at stimulating green innovation among firms operating in regions with good environmental quality. In contrast, mandatory regulations drive higher ISO 14001 certification rates among firms located in areas with poor environmental quality. This study offers insights into the internal and external motivators of firms’ environmental behavior, contributing to the literature on corporate environmental responsibility. Additionally, it provides policy recommendations to encourage active participation in environmental initiatives among maritime manufacturing firms.